The Shackles of Patriarchy in the Short Story Collection Sepotong Hati yang Baru by Tere Liye: A Feminist Literary Sudy - Yunior, Az-Zahra Diva Rabbani; Hartono, Hartono; Wiyatmi, Wiyatmi (Journal of Language and Literature Studies, 2025)
This study aims to reveal the reflection of the patriarchal system and the social criticism of women’s oppression in three short stories by Tere Liye Kisah Sie Sie, Mimpi-Mimpi Sampek-Engtay, and Buat Apa Disesali. Using a feminist literary criticism approach, the study finds that patriarchy places women in a subordinate position through male dominance, social norms, and economic as well as cultural pressures. The female characters are portrayed as losing control over their own lives, becoming objects of social transactions, and being forced to submit to male authority. The findings indicate that patriarchy is not only physical and structural but also forms a symbolic power that instills obedience and dependency in women. Through his works, Tere Liye presents a sharp critique of gender inequality and calls for the importance of equality, legal protection, and social reform so that women can become subjects of their own lives. In this research, data were collected through a literature review method by closely examining the forms of patriarchy depicted in Tere Liye’s short story collection Sepotong Hati yang Baru. Overall, Tere Liye delivers a strong criticism of the patriarchal system, illustrating how women are often disadvantaged and denied the space to become active subjects in their own existence.